Material comprising hard carbon
Patent Information
- Application Number
- CN202580024292.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-24
- Filing Date
- 2025-01-23
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies struggle to effectively recycle and reuse hard carbon materials that have been cycled in sodium-ion batteries, resulting in poor electrochemical performance in these batteries and a lack of efficient recycling methods.
By recovering hard carbon materials from spent sodium-ion batteries, removing unwanted inorganic impurities, and then pyrolyzing them at high temperatures, hard carbon materials with low specific surface area and low impurity content are formed, which can be used to prepare negative electrode active materials.
This study achieved efficient recovery of hard carbon materials from spent sodium-ion batteries, resulting in the preparation of high-performance negative electrode active materials suitable for sodium-ion batteries. This reduced the first cycle loss and increased the second cycle capacity.
Smart Images

Figure CN123036254A_ABST
Abstract
Description
[0001] Field of invention
[0002] This invention relates to a method for preparing a material containing hard carbon. The invention also relates to a material containing hard carbon that can be obtained by the method of this invention. Furthermore, the invention relates to uses incorporating hard carbon.
[0003] Background of the invention
[0004] Sodium-ion batteries are similar in many ways to the commonly used lithium-ion batteries of today; both are reusable secondary batteries comprising an anode (negative electrode), a cathode (positive electrode), and electrolyte materials; both are capable of storing energy; and both are charged and discharged through similar reaction mechanisms. When a sodium-ion (or lithium-ion) battery is charged, Na... + (or Li) + Ions deintercalate from the cathode and intercalate into the anode. Simultaneously, charge-balancing electrons travel from the cathode through the external circuitry containing the charger and enter the anode of the battery. The same process occurs during discharge, but in the reverse direction.
[0005] Sodium-ion batteries include a layer of active material coated on a current collector foil to form the cathode, and a similar structure exists for the corresponding anode. The cathode and anode are physically separated by a separator that allows ions to flow within a liquid electrolyte medium, which is uniformly present within the battery and wets the entire cathode, anode, and separator. During charging, Na… + Ions shuttle from the cathode active material and embed into the anode active material (electrons flow through the external circuit), and the reverse process occurs during discharge (sodium ions are extracted from the anode active material and embed into the cathode active material, electrons flow through the external circuit and do useful work).
[0006] Graphite-form carbon has been favored as an anode material in lithium-ion batteries for some time due to its high gravimetric and volumetric capacity; graphite electrodes offer reversible capacities exceeding 360 mAh / g, comparable to the theoretical capacity of 372 mAh / g. The electrochemical reduction process involves Li... + Ions are embedded between graphene layers to produce LiC6. However, graphite is much less electrochemically active to sodium, and sodium has a much larger atomic radius than lithium, which severely limits the embedding of graphene layers in the graphite anode in sodium-ion batteries.
[0007] On the other hand, it was found that anodes made of hard carbon materials (such as those described in PCT / GB2020 / 050872, US2002 / 0192553A1, US9,899,665B2, and US2018 / 0287153A1) performed much better in sodium-ion batteries.
[0008] Hard carbon possesses a disordered structure, overcoming many of the problems associated with sodium ion insertion. The exact structure of hard carbon materials remains to be determined, but generally, it is described as a non-graphitizable carbon material lacking long-range crystalline order. Hard carbon has multiple layers, but these layers are not neatly stacked over long distances, and it is a microporous material. Despite the lack of a definable crystal structure, hard carbon is isotropic at the macroscopic level. One reason for the difficulty in constructing a general structural model for hard carbon is that short-range order, domain size, and the ratio of carbon layers to micropores depend on synthesis conditions such as the carbon source, carbonization, and pyrolysis temperatures.
[0009] Furthermore, unlike graphite, which has a multi-layered crystalline structure in which carbon planes are stacked, hard carbon has a disordered layered structure in which carbon planes are stacked in a state of displacement in three dimensions. Therefore, even at high temperatures (e.g., 3000°C), heat treatment of hard carbon does not lead to a transformation from a disordered layered structure to a graphite structure, or to the development of graphite crystallites. Thus, hard carbon is structurally distinct from graphite and can be said to contain one or more non-graphitized domains and one or more non-graphitized domains.
[0010] Sodium-ion batteries have attracted considerable interest and are considered a promising candidate for next-generation battery technology. Therefore, with the anticipated increase in "waste" sodium-ion batteries, the efficient recycling of components from such batteries is environmentally attractive. Consequently, one area requiring greater attention is the development of new methods to achieve the efficient recovery of key components, such as negative electrode active materials, from "waste" sodium-ion batteries.
[0011] The review entitled “The Review of Existing Strategies of End-of-Life GraphiteAnode Processing Using 3Rs Approach: Recovery, Recycle, Reuse” (Batteries 2023, 9(12), 579) summarizes existing technologies for recovering graphite from “waste” lithium-ion batteries.
[0012] Notably, in "Mechanistic insights into the lattice reconfiguration of the anode graphite recycled from spent high-power lithium-ion batteries," Journal of Power Sources 2021; 481; 229159, Yu et al. emphasized the lattice defects present in the graphite anodes of recycled spent lithium-ion batteries. By comparing physical properties, namely graphite grain size, degree of graphitization, d-spacing, and defect density, as well as electrochemical performance, the authors concluded that relatively long-term annealing (ideally 6 hours) at high temperatures (ideally 3000°C) under certain inert atmospheres (preferably N2) is required to restore the properties of the recycled graphite to "battery-grade" levels. High graphitization is considered ideal and is typically achieved through annealing at high temperatures, as described in SGLCarbon's brochure entitled "The Capacity Boosters: our graphite-based battery solutions," which is available on the priority date of this application at https: / / www.sglcarbon.com / pdf / SGL-Brochure-SIGRACELL-The-Capacity- Boosters-EN.pdf get.
[0013] Furthermore, CN114583315A discloses a method for recycling graphite anodes that have been cycled in lithium-ion batteries. Specifically, Examples 1 and 2 disclose recycling methods for natural and artificial graphite anodes, respectively. These methods include a coating step in which the used graphite material is heated together with a carbon source to repair structural damage caused during graphite anode cycling. CN114583315A further applies this teaching to alternative carbon-based anode materials, such as hard carbon and mesoporous carbon. However, it is known that coating methods affect the microporosity of hard carbon in hard carbon anodes, which must be carefully controlled to minimize first-cycle losses and maximize second-cycle capacity. CN114583315A does not provide any first-cycle loss or capacity data for its recycled material. Therefore, it is unclear whether the method of CN114583315A can be used to recycle hard carbon that has been cycled in electrochemical cells, particularly sodium-based electrochemical cells, to provide a negative electrode active material exhibiting low first-cycle losses and high second-cycle capacity.
[0014] Furthermore, it is unknown whether hard carbon anode materials prepared from “recycled” or “reclaimed” materials will be expected to exhibit acceptable electrochemical performance when used in electrochemical cells, such as sodium-ion batteries. Additionally, it is unknown whether “recycled” or “reclaimed” hard carbon anode materials will require “repair” in the same manner as graphite taught in CN114583315A.
[0015] Therefore, the present invention aims to overcome the aforementioned problems.
[0016] In particular, the object of the present invention is to provide a material comprising hard carbon that can be prepared using materials from “waste” sodium-based electrochemical batteries, especially sodium-ion batteries. Importantly, such a material will enable the preferred sodium-ion battery to cycle as efficiently as it does when using existing prior art materials, such as unused “raw” hard carbon. Ideally, this material will enable the preferred sodium-ion battery to cycle even more efficiently when compared to existing prior art materials, such as unused “raw” hard carbon.
[0017] The method for preparing the material will also contrast with existing techniques because it will enable the efficient recovery of hard carbon from "waste" sodium-based electrochemical batteries, preferably sodium-ion batteries. Furthermore, the method of the present invention will also enable the efficient and cost-effective production of materials containing hard carbon.
[0018] The present invention achieves these objectives by providing a method for preparing a material containing hard carbon, wherein the method comprises utilizing a composition containing hard carbon, wherein the hard carbon contained in the composition has undergone one or more charge and / or discharge operations in an electrochemical cell.
[0019] As used herein, the phrase “undergo one or more charge and / or discharge operations” is intended to cover one or more “partial” or “incremental” charge and / or discharge operations in an electrochemical battery, as well as one or more “complete” or “thorough” charge and / or discharge operations in an electrochemical battery.
[0020] Preferably, the hard carbon contained in the composition comprising hard carbon has undergone one or more charge and / or discharge operations in a sodium-based electrochemical cell.
[0021] As used herein, the term "sodium-based electrochemical battery" refers to any electrochemical battery in which the charging and / or discharging process involves the transfer of sodium and / or sodium ions between the positive and negative electrodes. Preferred sodium-based electrochemical batteries include sodium-ion batteries, sodium metal batteries, and anode-free sodium batteries.
[0022] Ideally, sodium-based electrochemical cells are sodium-ion cells, with sodium-ion full cells being the most preferred.
[0023] It should be understood that hard carbon compositions that have undergone one or more charge and / or discharge operations in sodium-based batteries, particularly sodium-ion batteries, can be identified by one or more of a variety of techniques known to those skilled in the art, such as inductively coupled plasma atomic emission spectrometry (ICP), energy-dispersive X-ray spectroscopy (EDX), or X-ray photoelectron spectroscopy (XPS). Preferably, hard carbon compositions that have undergone one or more charge and / or discharge operations in sodium-based batteries can be identified by inductively coupled plasma atomic emission spectrometry (ICP) and / or energy-dispersive X-ray spectroscopy (EDX), with inductively coupled plasma atomic emission spectrometry (ICP) being the most ideal method.
[0024] In one embodiment, the hard carbon sample that has not been cycled in a sodium-based electrochemical cell will contain between 0 ppm and 0.1% by weight of sodium, optionally measured by one of the foregoing using any suitable technique known to those skilled in the art. Therefore, in this embodiment, the hard carbon sample that has been cycled in a sodium-based electrochemical cell will preferably contain more than 0.1% by weight of sodium, optionally measured by one of the foregoing using any suitable technique known to those skilled in the art.
[0025] In an alternative embodiment, the hard carbon sample that has not been cycled in a sodium-based electrochemical cell will contain between 0 ppm and 0.2 wt% sodium, optionally measured by one of the foregoing methods using any suitable technique known to those skilled in the art. Therefore, in this embodiment, the hard carbon sample that has been cycled in a sodium-based electrochemical cell will preferably contain more than 0.2 wt% sodium, optionally measured by one of the foregoing methods using any suitable technique known to those skilled in the art.
[0026] In another alternative embodiment, the hard carbon sample that has not been cycled in a sodium-based electrochemical cell will contain between 0 ppm and 0.3 wt% sodium, optionally measured by one of the foregoing methods using any suitable technique known to those skilled in the art. Therefore, in this embodiment, the hard carbon sample that has been cycled in a sodium-based electrochemical cell will preferably contain more than 0.3 wt% sodium, optionally measured by one of the foregoing methods using any suitable technique known to those skilled in the art.
[0027] Preferably, the charging and / or discharging process of the sodium-based electrochemical battery does not involve the transfer of lithium and / or lithium ions between the positive and negative electrodes.
[0028] Preferably, the hard carbon sample that has been cycled in a sodium-based electrochemical cell will contain between 0 ppm and 0.2% by weight of lithium, optionally measured by one of the above-mentioned methods, using any suitable technique known to those skilled in the art.
[0029] The composition containing hard carbon is the "raw material" in the method of the present invention. In particular, it is a raw material containing hard carbon that has undergone one or more charge and / or discharge operations in an electrochemical battery.
[0030] Ideally, the method is used to prepare a hard carbon-containing material for use in metal-ion batteries, particularly sodium-based electrochemical batteries, very particularly sodium-ion batteries, and most particularly sodium-ion full batteries.
[0031] As used in this paper, the term "hard carbon" refers to non-graphitizable carbon materials that lack long-range crystalline order. Hard carbon has multiple layers, but these layers are not neatly stacked over long distances, and it is a microporous material. Despite the lack of a definable crystal structure, hard carbon is isotropic at the macroscopic level. One reason why it is difficult to construct a general structural model for hard carbon is that its short-range order, domain size, carbon layer fraction, and microporous structure depend on synthesis conditions such as the carbon source, carbonization, and pyrolysis temperatures.
[0032] Furthermore, unlike graphite, which has a layered crystal structure in which carbon planes (graphene) are stacked, hard carbon has a disordered layered structure in which carbon planes are stacked in a three-dimensional displacement state. Therefore, even at high temperatures (e.g., 3000°C), heat treatment of hard carbon does not lead to a complete transformation from the disordered layered structure to a graphite structure, or to the development of graphitic microcrystals. Thus, hard carbon is structurally distinct from graphite and can be said to contain one or more non-graphitized domains and one or more non-graphitized domains.
[0033] Unlike this invention, conventional methods for producing hard carbon materials involve heating carbon-rich starting materials in an anaerobic atmosphere to temperatures above 500°C. These carbon-rich starting materials include minerals such as petroleum coke and pitch coke; secondary plant-based materials such as sucrose and glucose; artificial organic materials such as polymeric hydrocarbons and other organic compounds such as resorcinol formaldehyde; animal-derived materials such as feces; and primary plant-derived materials such as coconut shells, coffee beans, straw, bamboo, rice husks, banana peels, etc.
[0034] In one embodiment, the hard carbon contained in the composition has undergone four or more charge and / or discharge cycles in an electrochemical cell. In another embodiment, the hard carbon contained in the composition has undergone twenty-five or more charge and / or discharge cycles in an electrochemical cell.
[0035] In some embodiments, the hard carbon contained in the composition has undergone one hundred or more charge and / or discharge cycles in an electrochemical cell. In another embodiment, the hard carbon has undergone five hundred or more charge and / or discharge cycles in an electrochemical cell.
[0036] Preferably, the electrochemical battery is a metal-ion battery, such as a sodium-ion battery, ideally a sodium-ion full cell. Preferably, the resulting material containing hard carbon is a negative electrode active material, preferably used in the electrochemical battery, such as a sodium-based electrochemical battery. Ideally, the resulting material containing hard carbon is a negative electrode active material for sodium-ion batteries.
[0037] Compositions containing hard carbon provide a “recyclable” hard carbon source, wherein the hard carbon in the composition has undergone one or more charge and / or discharge operations as defined above. Ideally, such “recycled” or “recoverable” hard carbon source is purified using the methods of the present invention to form a material (preferably a negative electrode active material) that can be readily used in electrochemical batteries, such as sodium-ion batteries.
[0038] Preferably, the method of the present invention further includes:
[0039] a) Provide a composition comprising hard carbon, wherein the hard carbon in the composition has undergone one or more charge and / or discharge operations in an electrochemical cell, preferably a sodium-based electrochemical cell;
[0040] b) Treat the composition from step a) to remove any unwanted inorganic impurities; and
[0041] c) The treated composition is pyrolyzed at a temperature of about 600°C to 3000°C to form a material containing hard carbon.
[0042] The composition provided in step a) is likely to contain unwanted inorganic impurities. Such impurities may be due to the hard carbon contained in the composition having previously undergone one or more charge and / or discharge operations in an electrochemical cell. Alternatively, they may be due to the manner in which the composition in step a) is provided. In fact, as explained in more detail below, the composition in step a) is ideally provided by disassembling one or more electrochemical cells, meaning that the composition may be contaminated by impurities generated by other components in one or more electrochemical cells during the disassembly process. For example, the composition in step a) may contain impurities originating from one or more positive electrode active materials; and / or one or more positive electrode active materials themselves; and / or one or more binder components; and / or one or more electrolytes in such one or more electrochemical cells.
[0043] In one embodiment, the composition provided in step a) may contain 0.2% or more inorganic impurities by weight, optionally 1% or more inorganic impurities by weight. In another embodiment, the composition provided in step a) may contain 10% or more inorganic impurities by weight. In yet another embodiment, the composition provided in step a) may contain about 1 to 50% inorganic impurities by weight.
[0044] Undesirable inorganic impurities refer to, for example, impurities containing metals and / or nonmetals that may adversely affect electrochemical performance when the resulting hard carbon is used as a negative electrode active material. Examples of these may include metallic or nonmetallic elements, metal ions (e.g., transition metal ions, alkali metal ions, or alkaline earth metal ions), metals in elemental form, metals in compound form (e.g., oxides), nonmetallic ions, compositions, salts, and ligands.
[0045] In a preferred embodiment, step a) includes providing a composition (i.e., an initial composition) comprising hard carbon contaminated with one or more elements selected from Na, Cu, Ni, Mn, Mg, Ca, B, K, F, Ti, Al, Fe, P, Si, Zr, V, N, and O. Such elements may be present in ionic or non-ionic form. Therefore, in this embodiment, step b) may include treating the composition to remove one or more elements selected from Na, Cu, Ni, Mn, Mg, Ca, B, K, F, Ti, Al, Fe, P, Si, Zr, V, N, and O.
[0046] In one embodiment, elements selected from Ni, Mn, Mg, Ti, Al, Cu, and Fe can be impurities originating from one or more cathode active materials such as sodium transition metal oxides. Similarly, elements selected from Na, F, and P, especially F and P, can be impurities originating from one or more electrolytes such as NaPF6. More specifically, F can also be an impurity from other electrolytes such as NaBF4, NaFSI, and NaTFSI.
[0047] Ideally, step b) may include treating the composition to remove one or more elements selected from Na, Ni, Mn, Mg, Fe, Ti, Al, and Cu. In fact, such elements (which may include, for example, salts of Ni, Mn, Mg, Fe, Ti, Al, and Cu) can be isolated and then converted into more useful forms (e.g., metallic Ni, by electroplating or reduction using NaBH4, or NiO / NiCO3, by ion exchange reaction with Na2CO3 or NaOH, i.e., via the standard route).
[0048] Therefore, in a preferred embodiment, the method of the present invention not only advantageously recovers hard carbon that has undergone one or more charge and / or discharge operations in an electrochemical cell, but also recovers elements such as Ni, Mn and Mg.
[0049] In another embodiment, the method includes providing a composition (i.e., an initial composition) comprising hard carbon contaminated with two or more elements selected from Na, Cu, Ni, Mn, Mg, Ca, B, K, F, Ti, Al, Fe, P, Si, Zr, V, N, and O. Therefore, in this embodiment, step b) may include treating the composition to remove two or more elements selected from Na, Cu, Ni, Mn, Mg, Ca, B, K, F, Ti, Al, Fe, P, Si, Zr, V, N, and O.
[0050] In another embodiment, step b) may include treating the composition to remove two or more elements selected from Ni, Mn, Mg, Fe, Ti, Al, and Cu. In yet another embodiment, step b) may include treating the composition to remove all Ni, Mn, Mg, Fe, Ti, and Al.
[0051] However, to avoid any doubt, while the composition containing hard carbon (i.e., the initial composition) may be contaminated with the impurities described above, the composition may also contain other unwanted impurities in addition to those described above. These additional impurities may include carbonaceous impurities (e.g., carbonates and / or organic acid salts).
[0052] Therefore, a key objective of this invention is to provide a final material comprising hard carbon that is free of or contains very low amounts of unwanted inorganic impurities. Therefore, preferably, in step b) of this invention, the composition comprising “recycled” or “recovered” hard carbon in step a) is treated to substantially remove any unwanted inorganic impurities.
[0053] Ideally, the purity of the treated composition obtained at the end of step b) will preferably be at least 90%, i.e., it will be free of (0%) or contain a low level (<10% by weight) of inorganic impurities. In one embodiment, the treated composition obtained at the end of step b) will contain less than 10% by weight of inorganic impurities. Particularly preferably, the amount of inorganic impurities in the material produced at the end of step b) will be <5% by weight, more preferably <2% by weight, and particularly preferably from about 0 to about 0.6% by weight.
[0054] Processing step b) preferably involves the use of any suitable processing method or any suitable equipment known to those skilled in the art to separate and remove any unwanted organic and / or inorganic impurities from the composition provided in step a). Preferably, step b) of the invention includes the use of chemical digestion. This ideally results in elements such as Ni, Mn, Mg, Ti, and Al being present in the treated composition at an amount of about 0 to about 0.6% by weight at the end of step b).
[0055] Ideally, step b) comprises contacting the composition of step a) with acidic and / or alkaline conditions. Particularly preferably, step b) comprises contacting the composition of step a) with a washing solution to release at least a portion of unwanted inorganic impurities into the washing solution to form a treated composition.
[0056] Therefore, step b) of the present invention ideally involves chemical digestion, wherein the composition from step a) is contacted with a washing solution to dissolve unwanted inorganic impurities. Thus, step b) of the present invention can use a washing solution as an aqueous and / or non-aqueous solvent. Ideally, the washing solution is an aqueous solution and / or solvent selected from acid solutions, alkaline solutions, salt solutions, and water. Preferred step b) of the present invention uses an acid solution. Suitable acids may include one or more acids selected from hydrochloric acid, hydrofluoric acid, nitric acid, and sulfuric acid.
[0057] Ideally, the acid solution is preferably diluted. Preferably, the concentration of the acid solution is from about 1.0 M to about 3.0 M, and most preferably, the concentration of the acid solution is about 2.0 M. Particularly preferred is a 2.0 M hydrochloric acid solution.
[0058] Preferably, the washing solution (ideally an acidic solution) is hot, more preferably boiling. Suitable temperatures can be up to 150°C, more preferably 50°C to 120°C.
[0059] Ideally, the treatment in step b) is carried out in air and under atmospheric pressure. Such treatment is preferably carried out over a period of 30 minutes or more, optionally 1 hour or more, and most preferably 2 hours or more. In one embodiment, step b) includes contacting the composition from step a) with the washing solution for 30 minutes or more, ideally 1 hour or more, and most preferably 2 hours or more, to release at least a portion of the unwanted inorganic impurities into the washing solution.
[0060] In particular, when using acidic solutions, such as hydrochloric acid solutions, a contact time of about 1 hour to about 2 hours is especially preferred.
[0061] Optionally, the treated composition obtained at the end of step b) is separated (e.g., by filtration, preferably vacuum filtration) and preferably washed with one or more solvents until the pH of the filtrate reaches a certain range. Ideally, one or more solvents include water (preferably deionized water), and the pH of the filtrate is preferably about 5 to 6, more preferably 5.5 to 6. Optionally, the acid-treated material obtained in step b) is also dried, optionally using heating (preferably up to 150°C, more preferably 50°C to 120°C), and further optionally ground or milled, after which it is pyrolyzed in step c).
[0062] To avoid ambiguity, step b) may include one or more, optionally two or more, of the processing methods disclosed above. These may be performed simultaneously or sequentially.
[0063] Ideally, a pyrolysis step c) is needed to remove oxygen-containing compounds from the hard carbon surface at the end of step b), which has been treated as described above. In fact, such oxygen groups readily serve as permanent anchoring sites for injected charge carriers, causing initial cycle losses. Furthermore, it has been found that the specific surface area of the final negative electrode active material containing hard carbon determines the level of its irreversible capacity, while having a low specific surface area (100 m²) results in lower capacity. 2 This drawback is reduced in materials containing hard carbon (below / g); pyrolysis reduces the specific surface area of the final material to less than 50 m². 2 / g, preferably less than 10 m 2 The effect of / g.
[0064] Therefore, preferably, the specific surface area of the final material containing hard carbon obtained from step c) is less than 50 m². 2 / g, preferably less than 10 m 2 / g, more preferably 2 m 2 / g to 5 m 2 / g. All specific surface area values given in this application have been determined by BETN2 analysis.
[0065] Pyrolysis involves heating to the following temperatures over a period of 30 minutes to 8 hours: about 600°C to about 3000°C, preferably 750°C to 3000°C, more preferably 800°C to 2000°C, more preferably 1000°C to 1800°C, more preferably greater than 1000°C to 1750°C, more preferably 1100°C to 1700°C, and ideally around 1200°C. It is advantageous that oxygen is absent during pyrolysis, and oxygen is preferably replaced by a gas or mixture of gases selected from nitrogen, carbon dioxide, and inert gases such as argon.
[0066] Advantageously, a higher pyrolysis temperature of 750°C to 3000°C, preferably greater than 1000°C, enables the method of the present invention to remove a greater amount of impurities.
[0067] Following pyrolysis, the resulting pyrolysis material is subjected to conditional cooling / cooling to process the material. The resulting pyrolysis material is then optionally milled to provide a pyrolysis material having a d50 particle size of about 1 μm to about 25 μm, and more preferably about 8 μm to about 25 μm. An ideal d50 particle size is about 8 μm to about 12 μm.
[0068] Optionally, between steps (b) and (c) of the method of the present invention, a further step of carbonizing and / or drying the treated mixture at the end of step (b) can be performed. This can be carried out at a temperature of about 60°C to about 950°C.
[0069] In fact, it may be advantageous to perform a drying step on the treated composition at the end of step b) prior to pyrolysis to remove (e.g., by evaporation) any volatile compounds from the mixture. More specifically, the drying step can be carried out at a temperature of about 60 to 200°C, or at a temperature of about 80 to 250°C. It is preferable to carry out any drying under a non-oxidizing atmosphere, which may include one or more selected from nitrogen, carbon dioxide, and argon.
[0070] Alternatively or additionally, it may be advantageous to perform a carbonization step prior to pyrolysis to oxidize and / or carbonize (i.e., carbonization treatment) the treated composition at the end of step b). More specifically, the carbonization step in these cases can be carried out at temperatures ranging from about 250°C to about 950°C, preferably from about 400°C to about 850°C, more preferably from about 450°C to about 800°C, and ideally around 600°C. It is advantageous that oxygen is absent during carbonization, and oxygen is preferably replaced by a gas or mixture of gases selected from nitrogen, carbon dioxide, and inert gases such as argon.
[0071] Preferably, the carbonization process does not involve contacting the composition containing hard carbon with one or more other carbon-based materials. In particular, it is preferable that the composition containing hard carbon does not come into contact with any of graphite, graphene, or carbon nanotubes during the carbonization process.
[0072] Particularly preferably, the carbonization process does not involve contacting the composition containing hard carbon with carbon nanotubes at a temperature of about 400°C.
[0073] Following pyrolysis, the method of the present invention may further include step d), which involves contacting the material containing hard carbon with one or more carbon-containing materials at a temperature up to 950°C. Ideally, this will produce a material containing hard carbon having an outer surface containing one or more carbonized materials chemically bonded to the hard carbon material. Preferably, as determined using nitrogen BET analysis, the material containing hard carbon has 0 μm... 2 / g to 5 m 2 / g of open micropore specific surface area.
[0074] Preferably, step d) is performed after step c). Step d) can be performed immediately after step c), or after any number of intermediate steps following step c).
[0075] In fact, the final result of step d) will be the formation of chemical bonds, such as covalent bonds, between the hard carbon material and one or more carbide materials. Therefore, one or more carbide materials will be chemically bonded, preferably chemically deposited on the surface of the hard carbon material. In a particularly preferred embodiment, chemical vapor deposition is used in the contact step d) of the invention. Alternatively, the contact step d) of the invention includes plasma-enhanced deposition, atomic layer deposition, and physical vapor deposition.
[0076] Preferably, the carbon-containing material from which the carbonized material is obtained comprises a vapor and / or liquid and / or gas phase at at least one temperature of about 950°C or lower. Preferably, it comprises a vapor and / or liquid and / or gas phase at at least one temperature between about 200°C or higher and about 950°C or lower.
[0077] Step d) involves temperatures up to 950°C. A maximum temperature of 930°C is preferred, more preferably 900°C, and particularly preferably 880°C. An ideal temperature is 800°C. The process is carried out over a period of 10 minutes to 2 hours. It is advantageous that oxygen is absent during step d), and oxygen is preferably replaced by a gas or mixture selected from nitrogen, carbon dioxide, and inert gases such as argon.
[0078] Suitable carbon-containing materials from which carbonized materials are obtained can be selected from one or more organic and / or hydrocarbon materials, such as alkanes, alkenes, alkynes, or aromatics, which can be straight-chain, branched, cyclic, aliphatic, or aromatic. Secondary carbon-containing materials comprising one or more gaseous hydrocarbons having the following general formula are particularly preferred: C n H 2n+2 , where 1≤n≤10.
[0079] The preferred total pressure, total flow rate, and individual partial pressure and individual flow rate of carbon-containing materials are within the following ranges: 10 -6 Up to 3x10 7 Pa, 0.001 to 1000 L / min, 10 -6 Up to 3x10 7 Pa and 0.001 to 1000 L / min, and further preferably within the following ranges: 10 4 Up to 10 6 Pa, 0.01 to 100 L / min, 10 4 Up to 10 6 Pa and 0.01 to 100 L / min, and particularly preferably in the range of 5 × 10 4 Up to 5×10 5 Pa, 0.1 to 10 L / min, 5 × 10 4 Up to 5×10 5Pa and 0.1 to 10 L / min.
[0080] Optionally, the material containing hard carbon obtained at the end of step d) is dried, optionally using heating (preferably up to 150°C, more preferably 50°C to 120°C) and further optionally using vacuum, and then used as a negative electrode active material in an electrochemical cell.
[0081] Preferably, the obtained hard carbon material has a d50 particle size of about 1 μm to about 25 μm, and more preferably about 8 μm to about 25 μm. Preferably, the obtained hard carbon material has a d99 particle size of about 10 μm to about 50 μm, more preferably about 20 μm to about 40 μm, and more preferably about 20 μm to about 30 μm.
[0082] In one embodiment, the resulting hard carbon material can have a density of 100 m 2 A specific surface area of / g or less. Preferably, the obtained hard carbon material has a specific surface area of less than 50 m² / g. 2 / g, preferably less than 10 m 2 / g, more preferably 2 to 5 m 2 The specific surface area is 0 m² / g, as determined by nitrogen BET analysis. Preferably, the obtained hard carbon material has a specific surface area of 0 m² / g. 2 / g to 5 m 2 / g of open micropore specific surface area, as determined using nitrogen BET analysis.
[0083] Preferably, the obtained hard carbon material contains less than 5% or less than 2% inorganic impurities by weight. Ideally, the obtained hard carbon material has about 0 to about 0.6% inorganic impurities by weight. Preferably, the obtained hard carbon material has less than 0.1% inorganic impurities by weight.
[0084] Preferably, the hard carbon obtained has a carbon content of 95% or higher, ideally 99% or higher.
[0085] As described above, the composition containing hard carbon in step a) is ideally provided by dismantling one or more electrochemical cells, and preferably by dismantling one or more sodium-ion cells and / or anode-free sodium cells. In one embodiment, the composition containing hard carbon in step a) is provided by dismantling multiple electrochemical cells, for example, ten or more electrochemical cells.
[0086] In a preferred embodiment, the composition in step a) of the present invention is provided by means of:
[0087] i) Providing one or more electrochemical cells comprising one or more current collectors, said current collector comprising hard carbon, wherein the hard carbon has undergone one or more charge and / or discharge operations; and
[0088] ii) Separating hard carbon from at least a portion of one or more current collectors to form a composition containing hard carbon.
[0089] The one or more electrochemical cells provided in step i) are optionally one or more metal-ion cells and / or one or more sodium-based electrochemical cells, preferably one or more sodium-ion cells, such as sodium-ion full cells. Alternatively, the one or more electrochemical cells are one or more anode-free sodium cells and / or one or more sodium metal cells.
[0090] Preferably, one or more current collectors in step i) comprise hard carbon, wherein the hard carbon has undergone one or more charge and / or discharge operations in a sodium-based electrochemical cell. Ideally, the hard carbon has undergone one or more charge and / or discharge operations in a sodium-ion battery. Alternatively or additionally, the hard carbon has undergone one or more charge and / or discharge operations in a sodium metal battery and / or an anode-free sodium battery.
[0091] Preferably, one or more electrochemical cells may include one or more negative electrode (anode) electrodes, said negative electrode (anode) electrodes including a negative electrode current collector. Ideally, the negative electrode current collector includes hard carbon formed on one or more surfaces of the negative electrode current collector as a negative electrode active material. Such hard carbon has undergone one or more charge and / or discharge operations because one or more electrochemical cells have been charged and / or discharged.
[0092] Preferably, one or more electrochemical cells may further include one or more positive (cathode) electrodes, said positive (cathode) electrodes including a positive current collector. The positive current collector may include one or more positive active materials formed on one or more surfaces of the negative current collector. Such positive active materials may have undergone one or more charge and / or discharge operations, as one or more electrochemical cells have been charged and / or discharged.
[0093] The negative current collector, the positive current collector, or both the positive and negative current collectors can be made of aluminum or aluminum alloys (e.g., aluminum alloyed with one or more of Mg, Mn, Cr, Zn, Si, Fe, and Ni).
[0094] Preferably, one or more current collectors comprise aluminum. Preferably, the negative current collector comprises an aluminum current collector. Particularly preferably, both the negative and positive current collectors comprise aluminum. Alternatively, copper, magnesium, carbon paper / foil / substrate, and tin may also be used as current collector materials.
[0095] Preferably, one or more electrochemical cells may further include one or more binder components, ideally one or more polymer binder components. Such compounds are used to enable the negative electrode active material and / or positive electrode active material to bind to one or more surfaces of the negative electrode and / or positive electrode current collector.
[0096] Typically, the polymer binder component is selected from polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC).
[0097] Preferably, one or more electrochemical cells may further include one or more separators (typically polymer separators) and / or electrolyte compositions (typically non-aqueous electrolyte compositions).
[0098] Ideally, the unwanted inorganic impurities (e.g., compounds of Ni, Fe, Mn, Mg, Ti, Al, Na, and Cu) removed in step b) of the invention are typically derived from one or more positive electrode active materials that may be included in one or more electrochemical cells provided in step i).
[0099] Preferably, one or more positive electrode active materials are sodium-containing positive electrode active materials, ideally suited to allow sodium ions to be inserted / removed during charging / discharging. Examples of these may include sodium transition metal oxides, polyanionic compounds (including fluorinated polyanionic compounds), Prussian blue analog (PBA) compounds (such as Prussian white or Berlin green), materials that store sodium via conversion reactions, sodium transition metal fluorides, fluoride oxides, phosphates, sulfates, and silicates (and their fluorinated forms).
[0100] One or more preferred positive electrode active materials include sodium transition metal oxides. Preferred sodium transition metal oxides have the general formula:
[0101] A 1±δ M 1 V M 2 W M 3 X M 4 Y M 5 Z O 2-C
[0102] in,
[0103] A is one or more alkali metals selected from sodium, potassium, and lithium;
[0104] M 1 It contains one or more redox-active metals in the +2 oxidation state, preferably selected from nickel, copper, cobalt and manganese;
[0105] M 2 Includes metals in oxidation states greater than 0 and less than or equal to +4;
[0106] M 3 It includes metals in the +2 oxidation state;
[0107] M 4 Includes metals in oxidation states greater than 0 and less than or equal to +4;
[0108] M 5 It includes metals in the +3 oxidation state;
[0109] in,
[0110] 0≤δ≤1;
[0111] V>0;
[0112] W≥0;
[0113] X≥0;
[0114] Y≥0;
[0115] At least one of W and Y is >0
[0116] Z≥0;
[0117] C is in the range 0 ≤ c < 2
[0118] V, W, X, Y, Z, and C were selected to maintain electrochemical neutrality.
[0119] Ideally, metal M 2 Includes one or more transition metals, preferably selected from manganese, titanium, and zirconium; M 3 Preferably, it is selected from one or more of magnesium, calcium, copper, tin, zinc, and cobalt; M 4 Includes one or more transition metals, preferably selected from manganese, titanium, and zirconium; and M 5 Preferably, it is selected from one or more of aluminum, iron, cobalt, tin, molybdenum, chromium, vanadium, scandium, and yttrium.
[0120] Particularly preferred sodium transition metal oxides will have an O3 and / or P2 structure, and ideally, particularly preferred sodium transition metal oxides will comprise compounds having the general formula detailed above, which contain an O3 phase. Preferably, the sodium transition metal oxide will comprise compounds having the general formula detailed above, said compounds being in the form of a mixture of O3 and P2 phases. The ratio of O3 to P2 phase is 1 to 99: 99 to 1.
[0121] Since the composition in step i) contains one or more current collectors, the hard carbon must be separated from the one or more current collectors before step b), as required in step ii). In particular, in step ii), the hard carbon is separated from at least a portion (ideally substantially all) of the one or more current collectors to form the composition including hard carbon used in step a) of the present invention.
[0122] To avoid any doubt, the hard carbon separated in step ii) is not simply hard carbon, but is typically a mixture of components containing hard carbon. This is because hard carbon may contain one or more inorganic impurities derived from one or more positive electrode active materials in one or more electrochemical cells provided in step i); and / or one or more positive electrode active materials themselves; and / or one or more binder components; and / or one or more electrolytes.
[0123] Ideally, the separation in step ii) includes the use of one or more separation techniques selected from filtration, centrifugation, manual sorting, magnetic deflection, flotation, fluidization, crushing, heat treatment, drying, chemical extraction, chemical treatment (including washing with aqueous or non-aqueous solvents), flocculation, and combinations thereof.
[0124] Preferred heat treatment techniques may include a carbonization step, which may be carried out at about 250°C to about 950°C, preferably about 400°C to about 850°C, and ideally at a temperature of about 600°C. The purpose of such carbonization is to facilitate the detachment of hard carbon from one or more current collectors due to the decomposition of one or more binder components.
[0125] Preferred separation techniques include heat treatment in combination with one or more of manual sorting, crushing, or filtration. Alternatively, preferred separation techniques may include filtration without any heat treatment, for example, using a coarse filter to ideally remove substantially all portions of one or more current collectors.
[0126] In cases where one or more electrochemical cells additionally contain one or more negative electrode current collectors and / or one or more positive electrode current collectors and / or one or more separators, the above-described technique is also ideally used to separate hard carbon from at least a portion (ideally substantially all) of these components to form a composition containing hard carbon as used in step a) of the present invention.
[0127] As described above, the hard carbon-containing composition obtained from step ii) as used in step a) is generally impure and may contain 1% or more inorganic impurities by weight. For example, the hard carbon-containing composition obtained from step ii) may contain inorganic impurities derived from one or more positive electrode active materials from one or more electrochemical cells provided in step i); and / or one or more positive electrode active materials themselves; and / or one or more binder components; and / or one or more electrolytes. These inorganic impurities may be incorporated into the hard carbon provided in step i), and / or in step ii), due to the separation of the hard carbon from at least a portion (ideally substantially all) of one or more current collectors.
[0128] In a preferred embodiment, step ii) further includes:
[0129] iii) Disassembling one or more electrochemical cells provided in step i) to provide at least a portion of one or more current collectors comprising hard carbon, wherein the hard carbon has undergone one or more charge and / or discharge operations in the electrochemical cell, preferably a sodium-based electrochemical cell; and
[0130] iv) Separating hard carbon from at least a portion of one or more current collectors by means of heat treatment and / or chemical treatment to form a composition containing hard carbon.
[0131] It should be understood that steps iii) and iv) can be performed simultaneously. Preferred heat treatment techniques in step iv) may include a carbonization step, which may be performed at a temperature of about 250°C to about 950°C, preferably about 400°C to about 850°C, and ideally at about 600°C. Therefore, preferably, step iv) includes contacting at least a portion of one or more current collectors containing hard carbon with a temperature of about 250°C to about 950°C, preferably about 400°C to about 850°C, and ideally at about 600°C.
[0132] The purpose of such heat treatment is to cause the hard carbon to break off from one or more current collectors due to the decomposition of one or more polymer binder components.
[0133] The preferred chemical treatment in step iv) may include using one or more solvents to dissolve one or more polymer binder components, thereby causing the hard carbon to break off from one or more current collectors. Therefore, step iv) includes contacting at least a portion of the one or more current collectors containing the hard carbon with one or more solvents. Ideally, the one or more solvents dissolve one or more polymer binder compounds that enable the hard carbon to bind to one or more surfaces of the one or more current collectors.
[0134] Preferably, one or more solvents used in step iv) include water (preferably deionized water). Preferably, one or more solvents (ideally water) are hot. Suitable temperatures can be up to 150°C, more preferably 50°C to 100°C, and most preferably 70°C to 80°C. Step iv) is preferably carried out over a period of 30 minutes or longer, optionally 1 hour or longer, and preferably for about 1 hour.
[0135] The preferred chemical treatment in step iv) may also employ stirring (e.g., agitation) to induce the hard carbon to break off from one or more surfaces of one or more current collectors. Depending on the composition of the binder component, step iv) may also require pulverization to form an aqueous dispersion in order to successfully detach the hard carbon from one or more surfaces of one or more current collectors. In particular, when the binder component is water-soluble, step iv) preferably includes a pulverization process.
[0136] Preferably, at the end of the heat treatment and / or chemical treatment in step iv), the composition containing hard carbon is recovered by using one or more techniques selected from manual sorting, crushing, or filtration. Filtration is ideally used.
[0137] To avoid any doubt, the hard carbon separated and ultimately recovered in step iv) is not only hard carbon, but typically a mixture of components containing hard carbon. This is because hard carbon may contain one or more impurities derived from one or more positive electrode active materials in one or more electrochemical cells provided in the preceding stages of the method; and / or one or more positive electrode active materials themselves; and / or one or more binder components; and / or one or more electrolytes.
[0138] In a more preferred embodiment, since step iv) includes chemical treatment and / or heat treatment, it helps to induce hard carbon to detach from one or more current collectors by increasing the contact area of the chemical treatment and / or heat treatment.
[0139] Therefore, in a more preferred embodiment, step ii) further includes:
[0140] iii) Disassemble one or more electrochemical cells provided in step i) to provide one or more current collectors, the current collectors containing hard carbon, wherein the hard carbon has undergone one or more charge and / or discharge operations in the electrochemical cell, preferably a sodium-based electrochemical cell;
[0141] iv) Reduce one or more current collectors containing hard carbon into one or more parts;
[0142] v) Contacting the product of step iv) with heat treatment and / or chemical treatment;
[0143] and
[0144] vi) Separate the hard carbon from the product of step v) to form a composition containing hard carbon.
[0145] It should be understood that steps iii) and iv) can be performed simultaneously. With respect to the above embodiments, the preferred features of the heat treatment and / or chemical treatment in step v) can be further defined in the same manner as in step iv).
[0146] Preferably, steps iii) and iv) are performed simultaneously, and step v) includes chemical treatment.
[0147] It should be understood that the word "contacting" in step v) has the same meaning as "subjecting". Therefore, it would be equally appropriate to define step v) as "subjecting the product of step iv) to heat treatment and / or chemical treatment".
[0148] Step iv) of this embodiment preferably involves any suitable method or the use of any suitable equipment known to those skilled in the art to reduce one or more current collectors to one or more portions. Preferably, such a method may include chopping, cutting, mincing, grinding, milling, crushing, chewing, macerating, etc. Such a method may be performed manually or using suitable machines (e.g., shredders) known to those skilled in the art for performing such methods.
[0149] As used herein, the term "part" is intended to mean a portion of a whole. Therefore, the term as used herein is not intended to apply any particular size to a "part," as one or more current collectors can be ground into powder or pulverized into fine particles. Alternatively, one or more current collectors can be simply cut or chopped in half. Similarly, one or more parts can have different dimensions, or they can each have the same dimensions.
[0150] However, ideally, the size of one or more parts is approximately 0.5 cm each. 2 approximately 20 cm 2 Preferably about 1cm 2 approximately 15 cm 2 .
[0151] Step vi) in this embodiment requires separating hard carbon from the product of step v) to form a composition containing hard carbon. However, to avoid any doubt, the hard carbon separated in step vi) is not only hard carbon, but typically a mixture of components containing hard carbon. This is because hard carbon may include one or more impurities derived from one or more positive electrode active materials in one or more electrochemical cells provided in the preceding stages of the method; and / or one or more positive electrode active materials themselves; and / or one or more binder components; and / or one or more electrolytes.
[0152] Step vi) may use one or more separation techniques selected from manual picking, crushing, sorting (e.g., automated), flotation, magnetic deflection, or filtration. Ideally, when chemical processing is used in step v), the separation in step vi) is performed by filtration, such as using a coarse filter and / or vacuum filtration.
[0153] Ideally, when chemical treatment is used in step v), the separation in step vi) is performed in two steps. In this case, optionally the first step includes separating hard carbon from substantially all of one or more current collectors, and optionally the second step includes separating hard carbon from one or more solvents used in step v). Separation can be performed by filtration in both the first and second steps. However, a coarse filter can be used in the first step, while a finer filter can be used in the second step, and ideally, the second step may include the use of vacuum filtration.
[0154] Of course, in cases where one or more electrochemical cells additionally contain one or more negative electrode current collectors and / or one or more positive electrode current collectors and / or one or more separators, hard carbon can also be separated from at least a portion (ideally substantially all) of these components in step vi) to form a composition containing hard carbon as used in step a) of the present invention.
[0155] Optionally, the composition obtained at the end of step vi) is washed with one or more solvents, such as water (preferably deionized water), and then optionally dried, optionally using heating, ideally for 6 hours or longer, preferably 12 hours or longer.
[0156] In some cases, it may also be necessary to treat the composition obtained at the end of step vi) with one or more additional solvents before or after such optional washing and / or drying steps. This is useful for removing any residual polymer binder compounds present in the composition obtained at the end of step vi). This is especially true when step v) involves chemical treatment. The residual polymer binder compounds may comprise polyvinylidene fluoride (PVDF).
[0157] In this case, the optional step may include contacting the product of step vi) with one or more solvents to ideally remove PVDF. Preferably, the one or more solvents comprise dimethyl sulfoxide (DMSO), which is ideally heated to a temperature between 30°C and 120°C, and ideally between 60°C and 70°C. Preferably, such a step is carried out over a period of one hour or longer. The solvent-treated material obtained by heating (preferably up to 150°C, more preferably 50°C to 120°C) and further optionally filtering and drying under reduced pressure (preferably dynamic vacuum) is then used in step a) of the present invention.
[0158] In some cases, after step vi), the resulting composition containing hard carbon is optionally milled to provide a d50 particle size of about 1 μm to about 25 μm, and more preferably about 8 μm to about 25 μm. An ideal d50 particle size is about 8 μm to about 12 μm. Ideally, the milled composition containing hard carbon is then used in step (a) of the present invention.
[0159] On the other hand, the present invention also provides materials containing hard carbon that can be obtained by the methods disclosed herein.
[0160] On the other hand, the present invention also provides the use of materials containing hard carbon as disclosed herein in electrochemical batteries. Preferably, this aspect provides the use of materials containing hard carbon as disclosed herein in sodium-based electrochemical batteries. Ideally, this aspect provides the use of materials containing hard carbon as disclosed herein in sodium-ion batteries. Alternatively, this aspect provides the use of materials containing hard carbon as disclosed herein in anode-free sodium batteries and / or sodium metal batteries.
[0161] On the other hand, the present invention also provides an electrode comprising a material containing hard carbon as disclosed herein.
[0162] On the other hand, the present invention also provides an electrochemical battery comprising a material containing hard carbon as disclosed herein. Preferably, the electrochemical battery is a sodium-based electrochemical battery comprising a material containing hard carbon as disclosed herein.
[0163] Preferably, the electrochemical cell is selected from sodium metal batteries, sodium-ion batteries, and anode-free sodium batteries. Ideally, the electrochemical cell is a sodium-ion battery.
[0164] On the other hand, the present invention also provides the use of compositions containing hard carbon in the preparation of materials containing hard carbon, wherein the hard carbon in the composition has undergone one or more charge and / or discharge operations in an electrochemical battery. Preferably, the hard carbon contained in the composition has undergone one or more charge and / or discharge operations in a sodium-based electrochemical battery.
[0165] Preferably, the material containing hard carbon has a thickness of 100 m. 2 A specific surface area of / g or less. Preferably, the material containing hard carbon has a specific surface area of less than 50 m² / g. 2 / g, preferably about 10 m 2 / g, more preferably 2 m 2 / g to 5 m 2 The specific surface area is given in g. All specific surface area values given in this application have been determined by BET N2 analysis.
[0166] Preferably, as determined using nitrogen BET analysis, the material containing hard carbon has 0 m 2 / g to 5 m 2 / g of open micropore specific surface area.
[0167] Preferably, the material containing hard carbon has less than 2% inorganic impurities by weight.
[0168] On the other hand, the present invention also provides the use of a material containing hard carbon in an electrochemical battery, wherein the material containing hard carbon is made using a composition containing hard carbon, wherein the hard carbon in the composition has undergone one or more charge and / or discharge operations in the electrochemical battery. Preferably, the material containing hard carbon is used in a sodium-based electrochemical battery, such as a sodium-ion battery. Preferably, the hard carbon in the composition containing hard carbon has undergone one or more charge and / or discharge operations in a sodium-based electrochemical battery.
[0169] Preferably, materials containing hard carbon are used as negative electrode active materials in electrochemical cells, ideally in sodium-based electrochemical cells, such as sodium-ion batteries.
[0170] Preferably, the material containing hard carbon has a thickness of 100 m. 2 A specific surface area of / g or less. Preferably, the material containing hard carbon has a specific surface area of less than 50 m² / g. 2 / g, preferably about 10 m 2 / g, more preferably 2 m 2 / g to 5 m 2 The specific surface area is given in g. All specific surface area values given in this application have been determined by BET N2 analysis.
[0171] Preferably, as determined using nitrogen BET analysis, the material containing hard carbon has 0 m 2 / g to 5 m 2 / g of open micropore specific surface area.
[0172] Preferably, the material containing hard carbon has less than 2% inorganic impurities by weight.
[0173] In one embodiment, the hard carbon contained in the composition has undergone four or more charge and / or discharge cycles in an electrochemical cell. In another embodiment, the hard carbon contained in the composition has undergone twenty-five or more charge and / or discharge cycles in an electrochemical cell.
[0174] In some embodiments, the hard carbon contained in the composition has undergone one hundred or more charge and / or discharge cycles in an electrochemical cell. In another embodiment, the hard carbon has undergone five hundred or more charge and / or discharge cycles in an electrochemical cell.
[0175] Preferably, the electrochemical battery is a metal-ion battery, such as a sodium-ion battery, ideally a sodium-ion full battery. Preferably, the resulting material containing hard carbon is a negative electrode active material, ideally used in electrochemical batteries, such as sodium-ion batteries.
[0176] On the other hand, the present invention also provides the use of a material containing hard carbon as a negative electrode active material, wherein the material containing hard carbon is made using a composition containing hard carbon, wherein the hard carbon contained in the composition has undergone one or more charge and / or discharge operations in an electrochemical battery. Preferably, the hard carbon in the composition containing hard carbon has undergone one or more charge and / or discharge operations in a sodium-based electrochemical battery.
[0177] Preferably, the electrochemical cell is a metal-ion cell, such as a sodium-ion cell, and ideally a sodium-ion full cell.
[0178] Preferably, materials containing hard carbon are used as negative electrode active materials in electrochemical cells, ideally in sodium-based electrochemical cells, such as sodium-ion batteries.
[0179] Preferably, the material containing hard carbon has a thickness of 100 m. 2 A specific surface area of / g or less. Preferably, the material containing hard carbon has a specific surface area of less than 50 m² / g. 2 / g, preferably about 10 m 2 / g, more preferably 2 m 2 / g to 5 m 2 The specific surface area is given in g. All specific surface area values given in this application have been determined by BET N2 analysis.
[0180] Preferably, as determined using nitrogen BET analysis, the material containing hard carbon has 0 m 2 / g to 5 m 2 / g of open micropore specific surface area.
[0181] Preferably, the material containing hard carbon has less than 2% inorganic impurities by weight.
[0182] On the other hand, the present invention also provides a metal-ion battery comprising one or more negative electrodes, said negative electrode comprising at least one material comprising hard carbon, said material comprising hard carbon being made using a composition comprising hard carbon, wherein said hard carbon has undergone one or more charge and / or discharge operations in an electrochemical battery.
[0183] Ideally, the metal-ion battery will also include one or more positive electrodes, which preferably contain one or more positive electrode active materials, most preferably sodium-containing positive electrode active materials. Ideally, such materials are suitable for enabling sodium ion insertion / extraction during charging / discharging. Examples of these may include sodium transition metal oxides, polyanionic compounds (including fluorinated polyanionic compounds), Prussian blue analog (PBA) compounds (such as Prussian white or Berlin green), materials for storing sodium via conversion reactions, sodium transition metal fluorides, fluoride oxides, phosphates, sulfates, and silicates (and their fluorinated forms).
[0184] One or more preferred positive electrode active materials include sodium transition metal oxides. Preferred sodium transition metal oxides have the general formula described above.
[0185] Brief description of the attached figures
[0186] The invention will now be described with reference to the following figures, in which:
[0187] Figure 1A The image shows a scanning electron microscope image of the black material recovered from a 30 Ah sodium-ion battery after 633 cycles, according to Example 4.
[0188] Figure 1B The image shows an enlarged scanning electron microscope image of the black material recovered from a shredded 30 Ah sodium-ion battery after 633 cycles, according to Example 4.
[0189] Figure 1C The image shows a scanning electron microscope image of the demineralized hard carbon product of Example 4, which was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0190] Figure 1D The image shows a magnified scanning electron microscope image of the demineralized hard carbon product of Example 4, which was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0191] Figure 1E The image shows a scanning electron microscope image of the hard carbon product after carbonization treatment in Example 4, which was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0192] Figure 1F The image shows a magnified scanning electron microscope image of the hard carbon product after carbonization treatment in Example 4, which was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0193] Figure 1G The image shows a scanning electron microscope image of the hard carbon product after pyrolysis in Example 4, which was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0194] Figure 1H The image shows a magnified scanning electron microscope image of the hard carbon product after pyrolysis in Example 4, which was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0195] Figure 1I The image shows a scanning electron microscope image of the hard carbon product after CVD (chemical vapor deposition) in Example 4, which was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0196] Figure 1J The image shows a magnified scanning electron microscope image of the hard carbon product after CVD (chemical vapor deposition) in Example 4, which was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0197] Figure 2A The image shows a scanning electron microscope image of the demineralized hard carbon product of Example 4 after boiling in 2.0M HCl acid solution for 1 hour. The product was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0198] Figure 2B The image shows a magnified scanning electron microscope image of the demineralized hard carbon product of Example 4 after boiling in 2.0M HCl acid solution for 1 hour. The product was recovered from the black material of a 30 Ah sodium-ion battery after 633 cycles.
[0199] Figure 3 X-ray diffraction (XRD) patterns of hard carbon samples from various stages of the method in Example 4 are shown, the hard carbon samples being recovered from a 30 Ah sodium-ion battery that had been shredded after 633 cycles.
[0200] Figure 4 The image shows the weight loss of hard carbon samples from various stages of the method in Example 4 after oxidation in a thermogravimetric analyzer (TGA) under synthetic air. The hard carbon samples were recovered from a 30 Ah sodium-ion battery that had been shredded after 633 cycles.
[0201] Figure 5A The full-cell electrochemical performance of a control sodium-ion battery with a negative electrode active material is shown in the first and fourth cycles, where the negative electrode active material comprises Kuranode type 1 hard carbon.
[0202] Figure 5B The full-cell electrochemical performance of a sodium-ion battery having the negative electrode active material according to the invention is shown in the first and fourth cycles, wherein the negative electrode active material comprises hard carbon recovered according to Example 2, said hard carbon being derived from a battery that has undergone only four formation cycles.
[0203] Figure 5C The full-cell electrochemical performance of a sodium-ion battery having the negative electrode active material according to the invention is shown in the first and fourth cycles, wherein the negative electrode active material comprises hard carbon recovered according to Example 3, which was artificially removed from a 30 Ah sodium-ion battery after 594 cycles.
[0204] Figure 5D The full-cell electrochemical performance of a sodium-ion battery having the negative electrode active material according to the invention is shown in the first and fourth cycles, wherein the negative electrode active material comprises hard carbon recovered according to Example 4, said hard carbon being shredded black material from a 30 Ah sodium-ion battery after 633 cycles.
[0205] Figure 6A The cycling performance of a sodium-ion battery having a negative electrode active material according to the invention has been shown, the negative electrode active material having undergone 550 cycles in the sodium-ion battery, wherein the negative electrode active material comprises hard carbon recovered according to Example 4, the hard carbon being shredded black material from a 30 Ah sodium-ion battery after 633 cycles.
[0206] Figure 6B It shows Figure 6A Cyclic performance of a sister cell of a sodium-ion battery having a negative electrode active material according to the invention that has undergone 487 cycles, wherein the negative electrode active material comprises hard carbon recovered according to Example 4, the hard carbon being shredded black material from a 30 Ah sodium-ion battery after 633 cycles.
[0207] Figure 7 The top row shows scanning electron microscope images of hard carbon prepared according to Example 2 at various stages of processing, and the bottom row shows corresponding energy dispersive X-ray microscope images showing the presence or absence of certain elements after each processing step.
[0208] Figure 8The top row shows scanning electron microscope images of hard carbon prepared according to Example 3 at various stages of processing, and the bottom row shows corresponding energy dispersive X-ray microscope images showing the presence or absence of certain elements after each processing step.
[0209] Figure 9 The top row shows scanning electron microscope images of hard carbon prepared according to Example 4 at various stages of processing, and the bottom row shows corresponding energy dispersive X-ray microscope images showing the presence or absence of certain elements after each processing step. Example
[0210] Hard carbon materials were prepared according to the method of the present invention as detailed in Examples 2 to 4 below. Comparative Example 1 discloses the use of an anode from “raw” hard carbon (i.e., hard carbon that has not previously undergone one or more charge and / or discharge cycles in an electrochemical cell, such as a sodium-ion battery).
[0211] Abbreviations used:
[0212] EC = ethylene carbonate, DEC = diethyl carbonate, PC = propylene carbonate, PCS = 1,3-propanediol cyclosulfate, P123 = poloxamer, TMSB = tris(trimethylsilyl)borate.
[0213] General steps for manufacturing hard carbon sodium-ion batteries
[0214] Sodium-ion batteries are manufactured using a mixed-phase O3 / P2 oxide cathode, a hard carbon anode, and an electrolyte composition. Aluminum tabs are attached to each electrode, and the battery is encapsulated in a polymer-coated aluminum pouch.
[0215] General steps for cathode preparation
[0216] The cathode electrode is prepared by solvent casting of a slurry of active material, conductive carbon, binder, and solvent. In all embodiments, the cathode comprises an O3 / P2 nickelate oxide material as the cathode active material, polyvinylidene fluoride (PVDF) as the binder, and C65 as the conductive additive, which are coated on a carbon-coated aluminum foil current collector in a weight ratio of 92:03:05.
[0217] Anode preparation
[0218] Hard carbon anode (anode) electrodes are prepared by solvent casting of a slurry of hard carbon active material, conductive carbon, binder, and solvent using a doctor blade method. The conductive carbon used is C65 (Imerys). A mixture of sodium carboxymethyl cellulose (CMC) (Aquaion™ AQU D-5283 from Ashland) and styrene-butadiene rubber (SBR) (BM-451B from Zeon Europe GmbH), or polyvinylidene fluoride (PVDF), is used as the binder, and water is used as the solvent. The slurry is then cast onto carbon-coated aluminum foil and dried under vacuum at approximately 120°C.
[0219] General steps for preparing electrolytes
[0220] The electrolyte is prepared as follows. Appropriate amounts of solvent for the desired solvent system are mixed together in glass vials at the desired weight ratio. Where appropriate, one or more performance additives (e.g., one or more surfactants, one or more boron-containing compounds, one or more sulfur-containing compounds, or combinations thereof) are also added to prepare the solvent system. To dry the solvent mixture, activated 4Å molecular sieves are added, and the solvent mixture is dried for at least 18 hours.
[0221] In a separate glass flask equipped with a magnetic stirrer, add the desired weight of NaPFe salt, followed by the desired amount of the desired solvent mixture. Stir the salt and solvent mixture magnetically for at least 18 hours; the resulting electrolyte is then ready for use.
[0222] Please note that the weight percentages of various solvents and / or functional additives are relative to the total weight of the solvent system (they do not include the weight of one or more sodium salts).
[0223] Constructing a battery
[0224] After coating the cathode and anode, they are stamped to the desired dimensions. The coating weight of the cathode and anode is expressed in GSM values (grams per square meter), which refers to the areal density of the electrode active material layer.
[0225] The separator used is a typical polyolefin separator, such as Celgard 2500. Inside a glove box, the cathode / separator / anode assembly is placed in a pouch with two aluminum-based connecting tabs serving as terminals, and filled with an appropriate amount of liquid electrolyte. These pouch batteries are then sealed in the glove box and removed for battery testing.
[0226] Battery test
[0227] The battery is tested using constant current (constant current) cycling technology. Generally, the battery is first charged to a predetermined maximum voltage limit in constant current (CC) mode. Then, as shown in the embodiments, the battery is subjected to a constant voltage (CV) step at this maximum voltage limit, either for a predetermined time or until the current drops to a predetermined value. In some embodiments, the battery is subjected to a series of different CC modes to different voltage values before undergoing the CV step only at the maximum voltage value. As shown, the discharge process is performed either in CC mode to a lower cutoff voltage or in constant power (CP) mode.
[0228] Commercial battery cyclers from MTI Inc. (Richmond, CA, USA) or Maccor (Tulsa, OK, USA) were used. During charging, alkali metal ions are embedded in the carbon-containing anode material. During discharging, alkali metal ions are extracted from the cathode active material and re-embedded in it.
[0229] All batteries underwent cycling tests at rates such as ±1C (which can also be expressed as ±C / 1), ±C / 5, or ±C / 10 (or other rates such as ±C / 50, as mentioned for each experiment). All batteries were allowed to stand for at least 4–24 hours before and after formation cycling.
[0230] Comparative Example 1: "Pristine" commercial hard carbon (Kuraray's Kuranode 1 type)
[0231] The negative electrode is constructed according to the general steps outlined above, wherein the slurry comprises 95 wt% hard carbon active material (Kuranode Type 1, supplied by Kureha), 3.5 wt% binder, and 1.5 wt% conductive additive material. The electrode coating weight is 50-60 g / m². 2 In fact, the hard carbon used as the negative electrode active material in this embodiment is "original" because it has not previously undergone one or more charge and / or discharge operations in an electrochemical battery.
[0232] Then, using the cathode prepared according to the general steps above, test the electrode using "raw" commercial hard carbon in half-cells and full-cells according to the following steps:
[0233] Half-cells were tested using Swagelok batteries at ±C / 20 within a voltage window of 0.001–2.0 V, followed by a forced sodium precipitation / stripping cycle to determine the true specific capacity of the hard carbon. The electrolyte in the half-cells was 1 M NaPF6 dissolved in a 1:2:1 PC:DEC:EC mixture, containing 1 wt% PCS and 1 wt% P123.
[0234] Full cells were tested in A7-sized double-layer pouch cells, using 1M NaPF6 dissolved in PC as the electrolyte, containing 20 wt% DEC, 2 wt% PCS, 1 wt% P123 and 1 wt% TMSB.
[0235] The full cell is formed at ±C / 10 within a voltage window of 1.0-4.1V, and then cycled 4 times. After formation, it is cycled 5 times each at ±C / 5, ±C / 3, +C / 3, and -1C within a voltage window of 1.8-4.1V, and then 1000 times at ±1C. After every 100 cycles, it is cycled 5 times at ±C / 5 as a check point.
[0236] Example 2: Hard carbon recovered from an anode electrode after 4 formation cycles
[0237] A 30 Ah (nominal) pouch cell was constructed using the battery preparation steps described above. The anode electrode comprised 95 wt% hard carbon active material (Type I Kuradone, supplied by Kureha), 3.5 wt% binder, and 1.5 wt% conductive additive material. The electrolyte used was 1 M NaPF6 dissolved in PC, containing 20 wt% DEC, 2 wt% PCS, 1 wt% P123, and 1 wt% TMSB. The 30 Ah pouch cell was then formed at ±C / 10 between 1.0 and 4.0 V, cycled four times, and then short-circuited and disassembled.
[0238] The separated anodes are then dried in a fume hood for at least 12 hours. The dried anode electrodes, containing 95% hard carbon, are then cut into 10-12 cm pieces. 2 Small pieces were then carbonized at 600°C for 2 hours under argon atmosphere.
[0239] After carbonization, the coating containing the negative electrode active material breaks off from the aluminum current collector due to the decomposition of the binder. The current collector is then manually separated, and the recovered anode coating powder is ground using a mortar and pestle.
[0240] The powder was then characterized using X-ray diffraction to confirm the presence of crystalline inorganic impurities. To remove any unwanted crystalline inorganic impurities (such as elements Na, P, and F derived from electrolytes) from the hard carbon, it was demineralized according to the following steps: 30 g of the recovered hard carbon was digested in 350 mL of boiling 2.0 M hydrochloric acid (HCl) solution for 1 hour. The demineralized hard carbon was filtered and washed with 5 L of boiling deionized water until the pH of the filtrate reached 5.5–6. The washed powder was then dried for at least 12 hours.
[0241] The demineralized powder was pyrolyzed at 1200°C for 1 hour under argon atmosphere. The pyrolyzed powder was then analyzed using a Malvern Mastersizer 3000 to obtain the particle size distribution. The powder was then optionally ground at 300 rpm for 30 minutes using a Retsch PM 100 planetary ball mill with an 80 mL agate jar and 10 10 mm agate balls until a median particle size of 8–12 micrometers was achieved.
[0242] Then, in a chemical vapor deposition reactor, under argon atmosphere at a temperature of 800-950°C, using formula C... n H 2n+2 The powder is surface-treated with alkanes of 1 ≤ n ≤ 10. The powder is then vacuum-dried at 120°C for at least 12 hours, and then coated onto an aluminum current collector using the following anode electrode formulation: 95 wt% active material; 3.5 wt% binder; and 1.5 wt% conductive additive. The electrode coating has a weight of 50-60 g / m². 2 .
[0243] Then, the electrodes were tested in both half-cell and full-cell batteries according to the following steps:
[0244] Half-cells were tested using Swagelok batteries at ±C / 20 within a voltage window of 0.001–2.0 V, followed by a forced sodium precipitation / stripping cycle to determine the true specific capacity of the hard carbon. The electrolyte in the half-cells was 1 M NaPF6 dissolved in a 1:2:1 PC:DEC:EC mixture, containing 1 wt% PCS and 1 wt% P123.
[0245] Full cells were tested in A7-sized double-layer pouch cells using 1M NaPF6 dissolved in PC as the electrolyte, containing 20 wt% DEC, 2 wt% PCS, 1 wt% P123, and 1 wt% TMSB. Full cells were formed at ±C / 10 within a voltage window of 1.0–4.1V and cycled 4 times. After formation, the cells were cycled 5 times each at ±C / 5, ±C / 3, +C / 3, and -1C within a voltage window of 1.8–4.1V, and then 1000 times at ±1C. A checkpoint was established after every 100 cycles at ±C / 5.
[0246] Example 3: Hard carbon recovered from the anode electrode manually stripped from a 30Ah pouch cell after 594 cycles
[0247] A 30 Ah pouch cell (nominal) was constructed using the battery preparation steps described above. The anode electrode comprised 95 wt% hard carbon active material (Type I Kuradone, supplied by Kureha), 3.5 wt% binder, and 1.5 wt% conductive additive material. The electrolyte used was 1M NaPF6 dissolved in PC, containing 20 wt% DEC, 2 wt% PCS, 1 wt% P123, and 1 wt% TMSB. The anode utilization was 180–190 mAh / g. The 30 Ah pouch cell was then formed at ±C / 10 between 1.0–4.0V and cycled 4 times. The first cycle had a coulombic efficiency of 87.5% and was cycled between 2.0–4.2V. The cells were charged at a constant current (CC) of C / 2 using a constant voltage (CV) until the current was reduced to one-tenth. This was followed by discharge at ±1C at a constant power (CP) of 35W for 594 cycles, after which the cells were short-circuited and disassembled.
[0248] The anode electrode is then removed. After separation from the battery, the anode electrode is immersed in deionized water to remove any residual sodium that may remain. The electrode is then dried at 80°C. The dried anode electrode is then cut into 10-12 cm pieces. 2 Small pieces were then carbonized at 600°C for 2 hours under argon atmosphere.
[0249] After carbonization, the coating containing the negative electrode active material breaks off from the aluminum current collector due to the decomposition of the binder. The current collector is then manually separated, and the recovered anode coating powder is ground using a mortar and pestle.
[0250] The powder was then characterized using X-ray diffraction to confirm the presence of crystalline inorganic impurities. To remove unwanted crystalline inorganic impurities from the hard carbon, it was demineralized according to the following steps: The recovered hard carbon was digested in boiling 2.0 M hydrochloric acid (HCl) solution for 1 hour. The demineralized hard carbon was filtered and washed with boiling deionized water until the pH of the filtrate reached 5.5–6. The washed powder was then dried for at least 12 hours.
[0251] The demineralized powder was pyrolyzed at 1200°C for 1 hour under argon atmosphere. The powder was then analyzed and the particle size distribution was obtained using a Malvern Mastersizer 3000. The powder was then optionally ground at 300 rpm for 30 minutes using a Retsch PM 100 planetary ball mill with an 80 mL agate jar and 10 10 mm agate balls until a median particle size of 8–12 micrometers was achieved.
[0252] Then, in a chemical vapor deposition reactor, under argon atmosphere at a temperature of 800-950°C, using formula C... n H 2n+2(Where 1 ≤ n ≤ 10) Alkane is used to surface-treat the powder. The powder is then vacuum-dried at 120°C for at least 12 hours, and then coated onto an aluminum current collector using the following anode electrode formulation: 95 wt% active material; 3.5 wt% binder; and 1.5 wt% conductive additive. The electrode coating weight is 50-60 g / m². 2 .
[0253] Then, the electrodes were tested in both half-cell and full-cell batteries according to the following steps:
[0254] Half-cells were tested using Swagelok batteries at ±C / 20 within a voltage window of 0.001–2.0 V, followed by a forced sodium precipitation / stripping cycle to determine the true specific capacity of the hard carbon. The electrolyte in the half-cells was 1 M NaPF6 dissolved in a 1:2:1 PC:DEC:EC mixture, containing 1 wt% PCS and 1 wt% P123.
[0255] Full cells were tested in A7-sized double-layer pouch cells using 1M NaPF6 dissolved in PC as the electrolyte, containing 20 wt% DEC, 2 wt% PCS, 1 wt% P123, and 1 wt% TMSB. Full cells were formed at ±C / 10 within a voltage window of 1.0–4.1V for 4 cycles. Subsequent formation cycles were performed at ±C / 5, ±C / 3, +C / 3, and -1C within a voltage window of 1.8–4.1V for 5 cycles each, followed by 1000 cycles at ±1C. A checkpoint was established after every 100 cycles at ±C / 5 for 5 cycles.
[0256] Example 4: Hard carbon recovered from the black material of a 30 Ah pouch cell after 633 cycles.
[0257] A 30 Ah pouch cell (nominal) was constructed using the battery preparation steps described above. The anode electrode comprised 95 wt% hard carbon active material (Type I Kuradone, supplied by Kureha), 3.5 wt% binder, and 1.5 wt% conductive additive material. The electrolyte used was 1M NaPF6 dissolved in PC, containing 20 wt% DEC, 2 wt% PCS, 1 wt% P123, and 1 wt% TMSB. The anode utilization was 180–190 mAh / g. The 30 Ah pouch cell was then formed at ±C / 10 between 1.0–4.0 V and cycled 4 times. The first cycle had a coulombic efficiency of 87.4% and was cycled between 2.0–4.2 V, charged with a constant current (CC) at C / 2 and a constant voltage (CV) until the current was reduced to one-tenth. This was followed by a constant power (CP) discharge at 35 W for 587 cycles, after which the cells were short-circuited and disassembled. In this embodiment, the positive electrode (e.g., the cathode electrode) contains at least the following elements present in the positive electrode active material: Ni, Mn, Mg, Ti, and Al. Alternative positive electrode active materials doped with Cu and Fe were also investigated.
[0258] Ten anode electrodes, ten cathode electrodes, a separator, and a stack of pouch material were randomly removed from the disassembled battery and shredded into pieces approximately 1-3 cm in size. 2 The fragments were poured into a beaker and placed on a heating plate containing deionized water at a temperature of 70-80℃.
[0259] The mixture was then vigorously stirred for 1 hour to allow the coating to peel off from both the anode and cathode electrodes of the aluminum anode and cathode current collector. The cathode coating was completely pulverized and dispersed in deionized water, while the cathode coating was only peeled off from the current collector without being pulverized and dispersed, because the PVDF binder of the cathode electrode is insoluble in water.
[0260] Insoluble and non-dispersible components, such as the diaphragm and stripped aluminum current collector, were filtered from the mixture using a coarse filter, leaving a black substance. The black substance was then vacuum filtered, rinsed three times in hot deionized water, and dried for at least 12 hours. To remove residual PVDF, 40 g of the black substance was dispersed in 150 mL of dimethyl sulfoxide (DMSO) and stirred at 60–70 °C for 1 hour. It was then vacuum filtered again to remove the solvent, dried, and ground using a pestle and mortar.
[0261] The powder was then analyzed and its particle size distribution was obtained using a Malvern Mastersizer 3000. The powder was then optionally ground at 300 rpm for 30 minutes using a Retsch PM 100 planetary ball mill with an 80 mL agate jar and 10 10 mm agate balls until a median particle size of 8–12 micrometers was achieved.
[0262] To demineralize and separate the hard carbon, 30 g of the black substance was dispersed in 350 ml of boiling 2.0 M HCl for 2 hours. The resulting demineralized hard carbon was then vacuum filtered and washed with 5 L of boiling deionized water until the pH of the filtrate reached 5.5–6. The demineralized hard carbon was then dried and ground into a fine powder.
[0263] The demineralized hard carbon was then carbonized at 600°C for 2 hours under argon atmosphere. The resulting carbonized hard carbon powder was then pyrolyzed at 1200°C for 1 hour under argon atmosphere. The particle size distribution of the pyrolyzed powder was then analyzed using a Malvern Mastersizer 3000.
[0264] Then, in a chemical vapor deposition reactor, under an argon gas flow, at a temperature of 800-950°C, using formula C... n H 2n+2 (Where 1 ≤ n ≤ 10) Alkane powder is surface-treated for 30 minutes. The treated powder is then vacuum-dried at 120°C for at least 12 hours, and then coated onto an aluminum current collector using the following anode electrode formulation according to the general procedure described above: 95 wt% active material; 3.5 wt% binder; and 1.5 wt% conductive additive. The electrode coating weight is 50-60 g / m². 2 .
[0265] Then, the electrodes were tested in both half-cell and full-cell batteries according to the following steps:
[0266] Half-cells were tested using Swagelok batteries at ±C / 20 within a voltage window of 0.001–2.0 V, followed by a forced sodium precipitation / stripping cycle to determine the true specific capacity of the hard carbon. The electrolyte in the half-cells was 1 M NaPF6 dissolved in a 1:2:1 PC:DEC:EC mixture, containing 1 wt% PCS and 1 wt% P123.
[0267] Full cells were tested in A7-sized double-layer pouch cells using 1M NaPF6 dissolved in PC as the electrolyte, containing 20 wt% DEC, 2 wt% PCS, 1 wt% P123, and 1 wt% TMSB. Full cells were formed at ±C / 10 within a voltage window of 1.0–4.1V for 4 cycles. Subsequent formation cycles were performed at ±C / 5, ±C / 3, +C / 3, and -1C within a voltage window of 1.8–4.1V for 5 cycles each, followed by 1000 cycles at ±1C. A checkpoint was established after every 100 cycles at ±C / 5 for 5 cycles.
[0268] result
[0269] Throughout the processing steps, the inorganic impurity content of the material in Example 4 was estimated at fixed intervals by calcining a partially dried powder (approximately 100 mg) in atmospheric air at 1000°C and weighing the residual ash. The results of these measurements are listed in Table 1 below and compared with the ash content of commercially available hard carbon.
[0270] Table 1
[0271]
[0272] These data indicate that processing the black material according to Example 4 produces a hard carbon material after chemical vapor deposition with a lower ash content than commercially available hard carbon materials (and therefore a lower content of inorganic impurities).
[0273] Figure 1A -J shows that when the black material of Example 4 undergoes further processing steps, impurities are reduced. That is, starting with the black material recovered from the shredded battery ( Figure 1A and 1B After demineralization ( Figure 1C and 1D After carbonization ( Figure 1E and 1F ); after pyrolysis ( Figure 1G and 1H ); and after CVD (Figures 11 and 1J).
[0274] Figure 2A and 2B It was also shown that after 1 hour in a boiling 2.0M HCl acid solution, cathode impurities remained in the black substance of Example 4, but these impurities were removed after 2 hours in a boiling 2.0M HCl acid solution. Figure 1C and Figure 1D ).
[0275] In addition, from Figure 7-9 Scanning electron microscope and energy dispersive X-ray microscope images show that the various elements that were initially present as inorganic impurities in the recovered hard carbon were removed after boiling in a 2.0 M HCl acid solution (“post-demineralization”).
[0276] In fact, Figure 7 The energy-dispersive X-ray spectroscopy results show that Na, Al, F, P and Si (which were present in the hard carbon recovered after the carbonization step in Example 2) were no longer present after 1 hour in a boiling 2.0 M HCl acid solution (“after demineralization”).
[0277] Figure 8The energy-dispersive X-ray spectroscopy results show that P, Na, Al, and F (which were present in the hard carbon recovered after the carbonization step in Example 3) were no longer present after 1 hour in a boiling 2.0 M HCl acid solution (“after demineralization”).
[0278] Figure 9 The energy-dispersive X-ray spectroscopy results show that Ni, Mn, Mg, Ti and Al (which were present in the initial black material of Example 4) were no longer present after 2 hours in a boiling 2.0 M HCl acid solution (“after demineralization”).
[0279] More particularly, and quite surprisingly, the method of the present invention is able to reduce the inorganic impurity content (e.g., ash content as shown in Table 1 for Example 4) in the initial black material "raw material," especially when such raw materials may contain impurities, such as one or more positively active materials, or impurities derived from more such positively active materials. In fact, the final hard carbon material after chemical vapor deposition has a lower level of impurity content than commercially available hard carbon. Having a low level of inorganic impurity content in the resulting final hard carbon material is important because inorganic impurities reduce its ability to be used as a negative electrode active material in sodium-ion batteries.
[0280] The products of each step in Example 4 were further analyzed by X-ray diffraction (XRD). X-ray diffraction analysis was performed using a Siemens (RTM) D5000 powder diffractometer to confirm the preparation of the desired target material, determine the phase purity of the product material, and identify the types of impurities present. Based on this information, the lattice parameters of the unit cell could be determined.
[0281] The general XRD operating conditions for analyzing materials are as follows:
[0282] Slit sizes: 2 mm, 2 mm, 0.2 mm
[0283] Range: 2θ = 10° - 60°
[0284] X-ray wavelength = 1.5418 Å (5 Å) (Cu Ka)
[0285] Speed: 1.0 second / step
[0286] Increment: 0.025°
[0287] The XRD data of the product of each step in Example 4 are as follows: Figure 3 As shown in the image.
[0288] Figure 4The TGA curves show that the hard carbon fully processed according to the method of the present invention has a purity of >99.97% by weight. It also shows that the initial black material contains approximately 53% by weight of used hard carbon and approximately 47% by weight of inorganic impurities, such as used cathode active material. It shows that after two hours of demineralization, the material has >99% by weight of carbon.
[0289] Table 2 below shows the physical properties of the hard carbon prepared according to each of Examples 1-4 above.
[0290] Table 2
[0291]
[0292] These data indicate that the method of the present invention does not significantly alter the median particle size compared to that shown in Comparative Example 1. Furthermore, while the BET surface area remains substantially unchanged, the micropore surface area is reduced by up to an order of magnitude. Finally, the recovered hard carbon exhibits a purity comparable to or slightly superior to that of the "original" hard carbon, as demonstrated by the reduced inorganic / ash content of the materials in Examples 2-4 compared to that of the material in Comparative Example 1. It is surprising that such a level of purity can be achieved, as discussed similarly above with reference to Table 1.
[0293] The electrochemical data of the half-cells prepared according to each of Examples 1-4 above are listed in Table 3 below.
[0294] Table 3
[0295]
[0296] These data indicate that the reversible and irreversible specific capacities of the half-cells of the anodes according to Examples 2-4, as well as the first-cycle coulombic efficiency, are comparable to those obtained for the control anode in Example 1.
[0297] Electrochemical data of the full cells prepared according to each of Examples 1-4 above are listed below. Figures 5A-5D , Figures 6A-6B And in Table 4 below.
[0298] Table 4
[0299]
[0300] These data indicate that the full-cell electrochemical data of the batteries containing the anodes according to Examples 2-4 are comparable to or improved compared to the values of the anode according to Example 1. Therefore, it is feasible to use the hard carbon material recovered according to Examples 2-4 as a negative electrode active material.
[0301] In particular, sodium-ion batteries containing such negative electrode active materials exhibit electrochemical performance equivalent to that of sodium-ion batteries containing "original" hard carbon. Therefore, the effects of this invention are particularly unexpected, since at the priority date of this application, it was not previously known whether it was possible to "recover" negative electrode active materials that had undergone one or more charge and / or discharge operations in an electrochemical battery.
Claims
1. A method for preparing a material comprising hard carbon, comprising the following steps: a) Provide a composition comprising hard carbon, wherein the hard carbon in the composition has undergone one or more charge and / or discharge operations in a sodium-based electrochemical cell; b) Process the composition in step a) to remove any unwanted inorganic impurities; and c) The treated composition is pyrolyzed at a temperature of about 600°C to about 3000°C to form a material containing hard carbon.
2. The method according to claim 1, wherein step b) comprises contacting the composition in step a) with acidic and / or alkaline conditions.
3. The method according to any one of claims 1 or 2, further comprising, between steps b) and c), carbonizing and / or drying the treated composition at the end of step b) at a temperature of about 60°C to about 950°C.
4. The method according to any one of claims 1 to 3, further comprising step d) after step c), step d) comprising contacting the material containing hard carbon with one or more carbon-containing materials at a temperature up to 950°C.
5. The method according to any one of claims 1 to 4, wherein the composition in step a) is provided by means of: i) Providing one or more electrochemical cells including one or more current collectors, said current collectors comprising hard carbon, said hard carbon having undergone one or more charge and / or discharge operations in a sodium-based electrochemical cell; and ii) Separate the hard carbon from at least a portion of one or more current collectors to form a composition comprising hard carbon.
6. The method of claim 5, wherein step ii) comprises: iii) Disassembling one or more electrochemical cells provided in step i) to provide at least a portion of one or more current collectors comprising hard carbon, wherein the hard carbon has undergone one or more charge and / or discharge operations in a sodium-based electrochemical cell; and iv) Separating the hard carbon from at least a portion of one or more current collectors by means of heat treatment and / or chemical treatment to form a composition comprising hard carbon.
7. The method of claim 5, wherein step ii) comprises: iii) Disassemble one or more electrochemical cells provided in step i) to provide one or more current collectors containing hard carbon, wherein the hard carbon has undergone one or more charge and / or discharge operations in a sodium-based electrochemical cell; iv) Reduce one or more current collectors containing hard carbon to one or more parts; v) Expose the product of step iv) to heat treatment and / or chemical treatment; and vi) Separate the hard carbon from the product of step v) to form a composition containing hard carbon.
8. The method of claim 7, wherein steps iii) and iv) are performed simultaneously, and step v) includes a chemical treatment.
9. The method according to any one of claims 1 to 8, wherein the hard carbon in the composition comprising step a) has undergone one or more charge and / or discharge operations in a sodium-ion battery.
10. The method of any one of claims 5 to 8, wherein the one or more electrochemical cells comprise one or more sodium-based electrochemical cells.
11. The method of any one of claims 1 to 10, wherein the pyrolysis temperature of step c) is from about 750 °C to about 3000 °C.
12. A material comprising hard carbon obtainable by the method of any one of claims 1 to 11.
13. Use of the material comprising hard carbon of claim 12 in an electrochemical cell.
14. An electrode comprising the material comprising hard carbon of claim 12.
15. An electrochemical cell comprising the material comprising hard carbon of claim 12.
16. The electrochemical cell of claim 15 selected from one or more of a sodium metal battery, a sodium-ion battery, and an anode-free sodium battery.
17. Use of a composition comprising hard carbon to make a material comprising hard carbon, wherein the hard carbon comprised in the composition has been subjected to one or more charging and / or discharging operations in a sodium-based electrochemical cell.
18. Use of a material comprising hard carbon in an electrochemical cell, wherein the material comprising hard carbon is made using a composition comprising hard carbon, wherein the hard carbon comprised in the composition has been subjected to one or more charging and / or discharging operations in a sodium-based electrochemical cell.
19. The use of claim 17 or 18, wherein the material comprising hard carbon has a BET (N2) specific surface area of 10 m2 / g or less as determined using nitrogen gas BET analysis. 2 / g or less as determined using nitrogen gas BET analysis.
20. The use of any one of claims 17-19, wherein the material comprising hard carbon has an open micropore specific surface area of 0 m 2 / g to 5 m 2 / g as determined using nitrogen BET analysis.
21. The use of any one of claims 17 to 20, wherein the material comprising hard carbon has less than 2% by weight of inorganic impurities.
22. The use of any one of claims 18 to 21 for a sodium-based electrochemical cell.
23. The use of claim 22 for a sodium-ion battery.
24. The use of any one of claims 18 to 23, wherein the material comprising hard carbon is used as a negative electrode active material.
Citation Information
Patent Citations
Method for recycling carbon negative electrode material from waste lithium ion battery
CN114583315A
Sodium ion batteries
US20020192553A1
Carbonaceous material for sodium ion secondary battery negative electrode, and sodium ion secondary battery using carbonaceous material for sodium ion secondary battery negative electrode
US20180287153A1
Sodium secondary battery comprising carbonaceous material
US9899665B2
